The clinical and psychological features of back pain in children and adolescents - S Yu Anisimova; Andrey Petrovich Rachin (Неврология, нейропсихиатрия, психосоматика, 2012)
Two hundred and ninety-two schoolchildren (41.1% boys and 58.9% girls) aged 6—17 years were examined by psychometric methods. Back pain was diagnosed in 29.1% of cases. The findings permitted the detection of certain characteriological personality traits in schoolchildren with back pain.